The Cold War, Alberta Labour, and the Social Credit Regime - Finkel, Alvin (Labour / Le Travail, 1988)
In the period following World War II, Alberta's Social Credit government passed several pieces of restrictive legislation which limited labour's ability to organize workers and to call strikes. The enforcement of labour law also reflected an anti-union bias. This article argues that Social Crediters, who had a penchant for conspiracy theories, believed that union militancy was the product of the manoeuverings of an international communist conspiracy. Their labour legislation was intended to foil the conspiracy's plans in Alberta and incidentally to reassure potential investors, particularly in the oil patch, of a good climate for profit-taking. But the path for such legislation was made smoother by the conservatism of one wing of the labour movement in the province and the fear of being tarnished with the communist brush by the other wing. On the whole, the Alberta experience casts a grim reflection on the theory that the post-war period provided a measure of industrial democracy for Canadian workers.
Keywords: Alberta; COLD War, 1945-1989; LABOR laws & legislation; LABOUR/LE Travail (Book); Labor; SOCIAL credit